Themes in contemporary art - Perry, Gillian. (Art of the 20th century (Yale University Press), 2004)
Inside the whale : an introduction to postmodernist art / Paul Wood -- Conceptual art, the aesthetic and the end(s) of art / Charles Harrison -- Post-conceptual painting : Gerhard Richter's extended leave-taking / Jason Gaiger -- Photography out of conceptual art / Steve Edwards -- I/eye/oculus : performance, installation and video / Kristine Stiles -- Dream houses : installations and the home / Gill Perry -- Art and globalisation / Niru Ratnam.